The genus Xenogenus Berg, 1883 (Heteroptera: Rhopalidae) in Chile - Faundez, Eduardo; Campodonico, Juan F. (My University, 2021)
The distribution of the species of Xenogenus Berg in Chile is addressed. The known distribution of Xenogenus gracilis (Reed), previously restricted to the O'Higgins region (besides Argentina, Bolivia, Brazil and Peru), is expanded up to Tarapaca and Los Rios regions. Xenogenus picturatum Berg (previously known from Argentina, Bolivia, Cuba, Mexico, Nicaragua, Uruguay and USA including Puerto Rico) is recorded for the first time in Chile, in the Metropolitan and Maule regions.
Keywords: coreoidea; faunistics; hemiptera; new records